Pengembangan Pkn Di Era Generasi Millenial Berbantuan M-Learning (Mobile Learning) Pada Gadget Pembelajaran Berbasis Cooperative Learning Bermuatan Karakter - Feri Wagiono; Syahrial Shaddiq; Aulia Akhrian Syahidi (research, training and philanthropy institution Natural Aceh, 2020)
Abstract: Study of the phenomenon of globalization spawned the cultural generation gadget, the term emergence of the millennial generation, or Generation Y aged 15-34 years. Technology utilization in youth to disseminate negative content such as violence, Asusila, conflict, and hoaxes. The Moral and deviant behavior of youth becomes a threat to Indonesia. The purpose of this article is the development of a millennial-generation PKn (citizenship education) curriculum for students SMA NU Palangka Raya. with a gadget-assisted Cooperative Learning Model. Research is approaches qualitative. The research subject consists of the principal, teacher, and students SMA NU Palangka Raya. Data Collection techniques in research using interview techniques, observations, and documentation. Development of a millennial-Generation PKn curriculum with models Cooperative Learning more effective assisted M-Learning (Mobile Learning) on gadgets makes a video or Indonesian film courses in PKn. Students can work together in groups to learn and be responsible for learning success. Hopefully, This model can help teachers in overcoming the condition of the students who have different abilities, the number of students, and solid learning. Students do not get bored quickly because they watch videos or the Indonesian movie with character. Abstrak: Studi tentang fenomena globalisasi melahirkan generasi budaya gadget, istilah munculnya generasi millenial atau generasi Y berusia 15-34 tahun. Pemanfaatan teknologi pada pemuda untuk menyebarkan konten negatif seperti kekerasan, asusila, konflik dan hoax. Moral dan perilaku menyimpang pemuda menjadi ancaman bagi Indonesia. Tujuan artikel ini ialah pengembangan kurikulum PKn (Pendidikan Kewarganegaraan) generasi millenal pada siswa SMA NU Palangka Raya berbantuan gadget dengan model cooperative learning bermuatan karakter. Penelitian ini adalah pendekatan kualitatif. Subjek penelitian terdiri dari kepala sekolah, guru dan siswa SMA NU Palangka Raya. Teknik pengumpulan data dalam penelitian menggunakan teknik wawancara, observasi, dan dokumentasi. Pengembangan kurikulum PKn generasi millenial dengan model cooperative learning lebih efektif berbantuan M-Learning (Mobile Learning) pada gadget membuat video atau film keindonesiaan mata pelajaran PKn. Siswa dapat bekerja sama dalam kelompok untuk belajar dan bertanggung jawab akan keberhasilan belajar. Diharapkan model ini dapat membantu guru dalam mengatasi kondisi siswa memiliki kemampuan berbeda, jumlah siswa banyak dan padatnya pembelajaran. Siswa tidak cepat bosan karena menonton video atau film keindonesiaan berkarakter.